Determination of Monoamine Oxidase Inhibition and Antioxidant Effects of Various Herbal Teas - Başak Yüce Dursun (Trakya University Journal of Natural Sciences, 2017)
The therapeutic properties of fruit teas are due to the polyphenolic flavonoids they contain. Compounds inhibiting the flavoenzyme monoamine oxidase (EC 1.4.3.4, MAO) are known to be used as medicines in treatment of neurodegenerative disorders such as Alzheimer’s and Parkinson’s diseases, and in various neurological disorders. There are many studies about natural compounds with antioxidant properties that prevent such diseases by reducing oxidative stress which plays an important role in neurodegeneration. It is therefore of particular importance to find double-acting products that can both inhibit monoamine oxidase and reduce oxidative stress. In this study, antioxidant activities of various fruit teas purchased from markets in Turkey were determined by ferric-reducing antioxidant power, cupric reducing antioxidant capacity and 1,1-diphenyl-2-picrylhydrazyl methods and their total phenolic contents were revealed. MAO enzyme inhibitions of these tea infusions was determined fluorometrically. The obtained results were compared with green and black tea bag infusions. The results showed that antioxidant and MAO inhibition properties of fruit tea samples were related to their total amount of phenolic substances they contained. Pomegranate containing tea infusions had higher antioxidant activity and phenolic content and exhibited high MAO inhibition. The results also showed that a MAO–B selectivity varying between 2 to 3,5-fold existed in various tea infusions with the highest value in rose hip tea. MAO inhibition abilities of tea infusions were demonstrated for the first time in this present study which was based on the fact that phenolic substances are responsible for MAO inhibition.